Exercise can improve sleep quality: a systematic review and meta-analysis - Banno, Masahiro (PeerJ, 2018)
BACKGROUND: Insomnia is common. However, no systematic reviews have examined the effect of exercise on patients with primary and secondary insomnia, defined as both sleep disruption and daytime impairment. This systematic review and meta-analysis aimed to examine the effectiveness/efficacy of exercise in patients with insomnia. METHODS: We searched the Cochrane Central Register of Controlled Trials, MEDLINE, Embase, PsycINFO, World Health Organization International Clinical Trials Registry Platform, and ClinicalTrials.gov to identify all randomized controlled trials that examined the effects of exercise on various sleep parameters in patients with insomnia. All participants were diagnosed with insomnia, using standard diagnostic criteria or predetermined criteria and standard measures. Data on outcome measures were subjected to meta-analyses using random-effects models. The Cochrane Risk of Bias Tool and Grading of Recommendations, Assessment, Development, and Evaluation approach were used to assess the quality of the individual studies and the body of evidence, respectively. RESULTS: We included nine studies with a total of 557 participants. According to the Pittsburgh Sleep Quality Index (mean difference [MD], 2.87 points lower in the intervention group; 95% confidence interval [CI], 3.95 points lower to 1.79 points lower; low-quality evidence) and the Insomnia Severity Index (MD, 3.22 points lower in the intervention group; 95% CI, 5.36 points lower to 1.07 points lower; very low-quality evidence), exercise was beneficial. However, exercise interventions were not associated with improved sleep efficiency (MD, 0.56% lower in the intervention group; 95% CI, 3.42% lower to 2.31% higher; moderate-quality evidence). Only four studies noted adverse effects. Most studies had a high or unclear risk of selection bias. DISCUSSION: Our findings suggest that exercise can improve sleep quality without notable adverse effects. Most trials had a high risk of selection bias. Higher quality research is needed.